Associations between Gilbert’s syndrome and personality characteristics - Düzenli,Tolga (2021)
Abstract Objective Gilbert’s syndrome (GS) is a benign genetic disorder that is characterized by intermittent mild jaundice in which the liver doesn’t process bilirubin properly. The aim of this study was to determine whether GS patients have a different personality structure and if there are associations between properties of temperament and character and total bilirubin levels. Methods A total of 1665 young male individuals aged from 19 to 30 who were admitted for occupational examinations were included in this study. Careful patient history was taken, a detailed physical examination was conducted, and hematologic and biochemical tests and abdominal ultrasonography were performed. The Turkish version of the Temperament and Character Inventory (TCI) was administered to all participants. 81 patients diagnosed with GS and 150 randomly chosen healthy individuals (control group) were investigated with comparison and correlation analyses. Results GS patients had higher scores than healthy controls for disorderliness (NS4) (p = 0.018), sentimentality (RD1) (p = 0.042), and fatigability (HA4) (p = 0.03). Moreover, Gilbert syndrome patients scored lower than controls for empathy (C2) (p = 0.041) and transpersonal identification (ST2) (p = 0.044). Bilirubin levels were positively associated with disorderliness (NS4) (r = 0.141, p = 0.032) and fatigability (HA4) (r = 0.14, p = 0.033). Conclusions GS patients may have some different personality characteristics from healthy individuals. This study is an initial exploration of the personality structure of GS patients and the findings should be interpreted with caution. Further prospective studies are needed to identify the relationship between Gilbert disease and personality characteristics.